The Relationship Between Academic Flow and Student Engagement Among Students of the Islamic Economics Department at UIN Alauddin Makassar - Auliyah, Himmah; Jalal, Novita Maulidya; Rasyid, Nurfajriyanti (Polteknik Ilmu Pemasyarakatan, 2025)
Academic flow is an optimal state in which individuals are focused and motivated and enjoy the learning process. One of the benefits of academic flow is that it increases student engagement in academic activities. This study explores the correlation between academic flow and student engagement among Islamic Economics majors at UIN Alauddin Makassar. A quantitative correlation research approach was used, involving 220 students as respondents. Data were obtained using measurement scales for student engagement and academic flow. Spearman's rho correlation analysis revealed a significant positive correlation between academic flow and student engagement (r = 0.560, p = 0.000). This indicates that higher academic flow scores are associated with higher student engagement scores. These findings have implications for research related to academic flow and student engagement and can inform the design of learning strategies that encourage optimal student engagement in higher education.